Os limites do desenho institucional: uma investigação empírica dos mecanismos da influência presidencial sobre as agências reguladoras independentes no Governo Federal brasileiro - Bonis, Daniel Funcia de (2016)
This study investigates empirically the issue of presidential influence over independent regulatory agencies (IRAs) in the Brazilian Federal Government in the period 1997-2014, focusing on the appointment process for senior positions of these bodies, through a mixed method of a sequential nature, combining qualitative and quantitative techniques. First, using the process tracing technique, a historical-comparative analysis of the genesis and consolidation of the ten federal IRAs in Brazil seeks to demonstrate the importance of the assumptions of credible commitment and institutional emulation as explanatory variables for the adoption of the model. Secondly, the presidential political influence on IRAs is measured by analyzing the pattern of vacancies for management positions, term completion rates, as well as the process of approval of presidential nominations by the Senate. Finally, we analyze the empirical data on the profile of the nominees for the IRAs management positions in the period, including variables such as party affiliation and professional qualifications, searching for indications of trade-offs between these two dimensions.